The Sports Industry's Function of Sports Testing and Measurement in the Provision of Physical Condition Assessment Services for KONI Medan City Athletes - Ramadan, Ramadan; Sibarani, Talenta Novila; Zega, Tety Nauli Yanti; Gulo, Tema Amati; Br Sembiring, Veby Yona; alfarizi, Umar; Putri, Tata Miranda; Tarigan, Vioni Zuriana; Tarigan, Viona Zuriana (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study aims to explore the role of sports testing and measurement as an industry within the sports sector, particularly in evaluating the physical condition of athletes in KONI Kota Medan. The study highlights the potential of sports graduates in this field and the necessary competencies required for success. Materials and Methods. This research uses a qualitative descriptive method with data collected through interviews, observations, and literature studies. Respondents included coaches, athletes, and sports measurement experts at KONI Kota Medan. The collected data were analyzed to understand the role of sports testing and measurement in the development of the sports industry. Results. The study identifies various physical tests, such as strength, speed, balance, VO2Max, flexibility, coordination, endurance, power, reaction time, and agility. The results indicate that sports testing and measurement play a significant role in performance evaluation, injury prevention, and training program development. However, challenges such as a lack of skilled professionals and the need for investment in equipment were identified. Conclusion. The findings suggest that sports testing and measurement have substantial potential in the sports service industry. To enhance this opportunity, it is necessary to train professionals, increase market awareness, and invest in facilities and equipment. KONI Kota Medan can lead the implementation of systematic evaluations to improve athlete performance sustainably.